P06.01 ROR1-CAR T-cells as novel treatment strategy for anaplastic thyroid carcinoma. (21st September 2022) - Chernyakov, D; Skorobohatko, O; Edemir, B; Nerger, K; Müller, T; Binder, M; Trojanowicz, B; Lorenz, K; Hüttelmaier, S; Alb, M; Hudecek, M; Dierks, C
Abstract : Background: Anaplastic thyroid carcinoma (ATC) and poorly differentiated thyroid carcinoma (PDTC) are rare thyroid malignancies with an extremely poor prognosis. Current therapies include operation, radiochemotherapy and kinase inhibitors, but finally most patients relapse and require further treatments. Thus, new therapeutic strategies are needed. CAR-T (chimeric antigen receptor) therapy is a modern approach to manipulate and target the patient's own T cells against a specific marker on tumor cells. The Receptor Tyrosine Kinase Like Orphan Receptor 1 (ROR1) is an essential transmembrane receptor during embryonic development and is associated with the non-canonical Wnt signaling pathway. ROR1 is barely expressed in adult healthy tissue, but can be re-upregulated on specific tumor cell types. In this study we investigated ROR1 as a potential target for CAR T-cell therapies in thyroid carcinoma. Materials and Methods: Initially, the expression of the ROR1 receptor was determined in primary ATC/PDTC and compared to non-malignant thyroid tissue. ROR1 mRNA expression on ATC cell lines was correlated with ROR1 surface expression as measured by flow cytometry. The efficiency of ROR1 directed CAR T-cell lysis was tested by co-incubating ATC cells together with ROR1-CAR T-cells in 2D cultures and 3D spheroid models and untransduced T-cells served as controls. To exclude cell line-based effects and to prove that the CAR T-cells specifically target ROR1-expressing cells, CRISPR/Cas9 was used to knock out ROR1 in three ROR1-positive ATC cell lines. Cytobead arrays were used to determine CAR T-cell activity. Results: Our date demonstrates an overexpression of ROR1 in ATC/PDTC compared to non-malignant thyroid tissue. In addition, three different ATC cell lines showed overexpression of ROR1, and we could show that pre-treatment with kinase inhibitors like Lenvatinib or Sorafenib does not affect ROR1 surface expression. ROR1positive ATC cell lines were efficiently lysed by ROR1-CAR T-cells in different 2D- and 3D cell culture models, while untransduced T-cells had no effect. The cytokine profile including IFN-γ, TNF-α and GM-CSF showed a specific activation of ROR1-CAR T-cells in the presence of ROR1 positive ATC cell lines. ROR1 knock out ATC cells were not affected by ROR1-CARTs and did not induce cytokine activation, thus proofing specificity for the target. Animal models are ongoing and will be finalized at presentation. Conclusions: In summary our data proof ROR1 as a viable and specific target for several types of thyroid carcinoma which is the basis for the design of a clinical phase I trial using ROR1-CAR T-cells in metastasized ATC and PDTC patients. Disclosure Information: D. Chernyakov: None. O. Skorobohatko: None. B. Edemir: None. K. Nerger: None. T. Müller: None. M. Binder: None. B. Trojanowicz: None. K. Lorenz: None. S. Hüttelmaier: None. M. Alb: None. M. Hudecek: None. C. Dierks: None.